Urgensi Penelitian Tindakan Kelas (PTK) untuk Meningkatkan Kualitas Pembelajaran pada Masa New Normal - Risma Firda Diana; Rohana Sufia; Ficky Dewi Ixfina (Pedagogik Journal of Islamic Elementary School, 2021)
The various kinds of obstacles occur in the learning process during the pandemic. One approach to solving learning problems is Classroom Action Research (CAR). The purpose of this study is to describe the urgency of CAR to improve the quality of learning in the new normal. This research method is descriptive and qualitative. The research subjects were active elementary teachers in East Java. The data collection instrument in this study was a questionnaire distributed online. The results of the study showed that 100% of the participating teachers thought that CAR was important to implement. This is because they benefit from the implementation of CAR, namely improving the quality of learning. However, the implementation of CAR during the pandemic experienced various obstacles including limited internet connection and face-to-face time. This is a challenge for teachers to continue to carry out CAR with the blended learning method to overcome learning problems that occur during the new normal period.Â